The tragedy of international organizations in a world order in turmoil - Jean-Jacques Hallaert (European Centre for International Political Economy (ECIPE), 2020)
China's rise and the U.S. response to the perceived threat it represents to its predominance jeopardize the world order and affect international institutions. The paralysis of the WTO and the U.S. withdrawal from the WHO are the most visible examples, but not the only ones. This article presents the case of the International Monetary Fund. Quotas are the cornerstone of IMF governance. They determine each member's contribution to the institution's resources and their voting power. As the world evolves, the quota distribution needs to be adjusted. Adjustments in quota shares and thus voting powers have always been politically difficult. However, they were possible. In the early 1990s, members agreed to an increase in the representation of Japan. In the 2000s, they agreed to increase substantially the voting power of emerging economies. In contrast, the 15th General Review of Quotas concluded early 2020, failed to increase and realign quotas. The proximate cause for this was the opposition of the United States to a change in quotas. This paper argues that the U.S. decision was in large part motivated to prevent an increased influence of China. The failure to increase and realign voting powers may have long-lasting consequences. In the absence of a quota increase, the IMF will need to continue to rely on borrowed resources to avoid a drop in its lending capacity. This extension of the "temporary" recourse to borrowed resources undermines the governance of the Fund as voting powers (which are not linked to borrowed resources but only to quotas) are disconnected from member's total contributions to the Fund and to their economic weight. This may trigger a new legitimacy crisis and provide incentives for countries like China to support the development of new and competing institutions which would better represent their interests and economic weight. Such a development would undermine the complex and fragile international financial architecture.
Keywords: 330